Stomach contents of the Early Jurassic fish †Lepidotes Agassiz, 1832 (Actinopterygii, Lepisosteiformes) and their palaeoecological implications. (3rd June 2021) - Thies, Detlev; Stevens, Kevin; Stumpf, Sebastian
ABSTRACT: Ginglymodian fishes formed one of the most dominant actinopterygian lineages during the Mesozoic, occurring in fully marine to freshwater depositional environments. However, although commonly preserved in Mesozoic strata around the world, there is little information on the feeding ecology of these fishes, which is mainly due to the scarcity of direct evidence of diet. Here we report two specimens of the ginglymodian fish † Lepidotes (Lepisosteiformes) from the Lower Jurassic of Germany that exhibit gastric contents consisting of small crustacean cuticle fragments indicative of shrimp-like taxa. The dentition of † Lepidotes, which is well adapted to such a diet, combined with its robust body shape and the position and shape of its fins, suggests that other potential food of the Early Jurassic † Lepidotes may have included moderately elusive, relatively soft-shelled or unprotected, free-living invertebrates. urn:lsid:zoobank.org